2018
DOI: 10.17016/2380-7172.2206
|View full text |Cite
|
Sign up to set email alerts
|

The Branch Puzzle: Why Are there Still Bank Branches?

Abstract: We provide evidence that the persistence of the large number of local bank branches across the country may be due to the fact that both depositors and small businesses continue to value local bank branches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Despite advances in mobile and online banking over time, the proportion of respondents citing branch locations as their most important reason has remained roughly the same since 1989 (between 43% and 49%). Also, from the 2016 SCF, of the 84 percent of households with bank accounts who reported visiting a branch in the past year, almost all did so to use services other than just an ATM (Anenberg, Chang, Grundl, Moore, and Windle 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite advances in mobile and online banking over time, the proportion of respondents citing branch locations as their most important reason has remained roughly the same since 1989 (between 43% and 49%). Also, from the 2016 SCF, of the 84 percent of households with bank accounts who reported visiting a branch in the past year, almost all did so to use services other than just an ATM (Anenberg, Chang, Grundl, Moore, and Windle 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A 2020 survey from the financial advisory firm Novantas found that most respondents wanted their banks to maintain branches close to where they live or work, and 70% of consumers felt having a branch nearby was important (Cocheo 2020). Community Reinvestment Act disclosures also reveal that nearby branches are still vital for small business borrowers, as the share of loans made by lenders without a local presence, while increasing, remains low (Anenberg et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation